2022
DOI: 10.1038/s41541-022-00556-z
|View full text |Cite
|
Sign up to set email alerts
|

B cells oppose Mycoplasma pneumoniae vaccine enhanced disease and limit bacterial colonization of the lungs

Abstract: Development of an effective vaccine for Mycoplasma pneumoniae has been hindered by reports of Vaccine Enhanced Disease (VED) in test subjects vaccinated and challenged in studies conducted in the 1960s. The exact mechanism of disease exacerbation has yet to be fully described, but host immune responses to Lipid-Associated Membrane Proteins (LAMPs) lipoprotein lipid moieties have been implicated. LAMPs-induced exacerbation appears to involve helper T cell recall responses, due in part to their influence on neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 78 publications
1
2
0
Order By: Relevance
“…Attachment could be blocked by pretreatment with vimentin antibody, indicating that vimentin might be one of the receptors for M. pneumoniae adherence to host cells. Gavitt et al showed that monoclonal antibodies to P1 adhesion protein could interfere with the adhesion of Mycoplasma pneumoniae ( 57 ), and our study found that the change of vimentin expression and the blocking of vimentin would also affect the adhesion of rP1-C and Mycoplasma pneumoniae , which provided a new idea for the prevention and treatment of Mycoplasma pneumoniae infection.…”
Section: Discussionsupporting
confidence: 61%
“…Attachment could be blocked by pretreatment with vimentin antibody, indicating that vimentin might be one of the receptors for M. pneumoniae adherence to host cells. Gavitt et al showed that monoclonal antibodies to P1 adhesion protein could interfere with the adhesion of Mycoplasma pneumoniae ( 57 ), and our study found that the change of vimentin expression and the blocking of vimentin would also affect the adhesion of rP1-C and Mycoplasma pneumoniae , which provided a new idea for the prevention and treatment of Mycoplasma pneumoniae infection.…”
Section: Discussionsupporting
confidence: 61%
“… 3 , 4 MP lacks a cell wall and is sensitive to beta-lactams, glycopeptides, and fosfomycin. 5 , 6 Owing to the small size of MP, it can spread via droplets and lead to an epidemic. 7 …”
Section: Introductionmentioning
confidence: 99%
“…3,4 MP lacks a cell wall and is sensitive to betalactams, glycopeptides, and fosfomycin. 5,6 Owing to the small size of MP, it can spread via droplets and lead to an epidemic. 7 The medications for MP infection primarily include quinolones, macrolides, and tetracyclines.…”
Section: Introductionmentioning
confidence: 99%